Kelayakan Ekstrak Daun Jambu Biji (Psidium guajava L.) sebagai Micellar Water dalam Menghambat Propionibacterium acnes - Keysha Alea Chairani; Eny Widhia Agustin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Acne (Acne vulgaris) is a skin problem often caused by Propionibacterium acnes bacterial infection. Guava leaves (Psidium guajava L.) contain antibacterial compounds, but their use as facial cleansing cosmetic preparations in the form of micellar water has not been widely done. This experimental study aims to determine the feasibility of guava leaf extract micellar water preparations in inhibiting the growth of Propionibacterium acnes. The preparations were formulated into two variations of extract concentration, namely F1 (50%) and F2 (100%). The evaluation stage of the preparations included organoleptic tests, homogeneity, pH, viscosity, and antibacterial activity testing using the well method. The results of physical tests showed that both formulas were liquid in texture, dark brown in color, and had a distinctive odor of guava leaves. However, the preparations were proven to be inhomogeneous due to the presence of particle deposits. The average pH value of the preparations was classified as acidic and was below the physiological standard of the skin (<4.5) which was 3.05 for F1 and 3.19 for F2. Antibacterial testing showed weak inhibition (<5 mm), with an average F1 inhibition zone of 0.961 ± 0.0300 mm and F2 of 1.142 ± 0.0226 mm. One-way ANOVA analysis showed a statistically significant difference between the treatment groups (p<0.05). However, the preparation was not yet clinically effective, thus concluding that guava leaf extract micellar water is not yet suitable for optimal application due to the physical instability triggered by the high extract concentration and its inadequate ability to penetrate the complex cell wall of Propionibacterium acnes. Further research is needed to optimize the formulation of this preparation.